Long‐Term SST Variability on the Northwest Atlantic Continental Shelf and Slope. Issue 1 (17th January 2020) - Chen, Zhuomin; Kwon, Young‐Oh; Chen, Ke; Fratantoni, Paula; Gawarkiewicz, Glen; Joyce, Terrence M.
Abstract: The meridional coherence, connectivity, and regional inhomogeneity in long‐term sea surface temperature (SST) variability over the Northwest Atlantic continental shelf and slope from 1982–2018 are investigated using observational data sets. A meridionally concurrent large SST warming trend is identified as the dominant signal over the length of the continental shelf and slope between Cape Hatteras in North Carolina and Cape Chidley, Newfoundland and Labrador, Canada. The linear trends are 0.37 ± 0.06 and 0.39 ± 0.06 °C/decade for the shelf and slope regions, respectively. These meridionally averaged SST time series over the shelf and slope are consistent with each other and across multiple longer observational data sets with records dating back to 1900. The coherence between the long‐term meridionally averaged time series over the shelf and slope and basin‐wide averaged SST in the North Atlantic implies approximately two thirds of the warming trend during 1982–2018 may be attributed to natural climate variability and the rest to externally forced change including anthropogenic warming. Plain Language Summary: This study investigates long‐term changes in the sea surface temperature (SST) since 1982 over the Northwest Atlantic continental shelf and slope. In particular, we focus on the changes consistently found from Cape Hatteras, North Carolina, United States, to Cape Chidley, Newfoundland and Labrador, Canada. The SST warming rates concurrently found over this large latitudinal range are 0.37 ± 0.06 and 0.39 ± 0.06 °C/decade for the shelf and slope regions, respectively. Analysis indicates that approximately two thirds of the warming trend during 1982–2018 may be attributed to natural climate variability and the rest to externally forced change including anthropogenic warming. Our findings are further confirmed by comparing with multiple other observational data sets. Key Points: Meridionally coherent surface warming is observed over the Northwest Atlantic continental shelf and slope The linear trends in SST exhibit distinct spatial maxima in the slope region off Georges Bank and Cape Hatteras Long‐term variations in the meridional means of SST are highly correlated with basin‐averaged values